Facile green synthesis of ZnO nanoparticles using natural-based materials: Properties, mechanism, surface modification and application. Issue 4 (August 2021) - Chan, Yin Yin; Pang, Yean Ling; Lim, Steven; Chong, Woon Chan
Abstract: An enormous amount of research had been dedicated to exploring the nanotechnology over the past decade. The fast-paced development of nanomaterial production has enhanced the application of zinc oxide (ZnO) in a wide variety fields. ZnO nanoparticles can be obtained mechanically or chemically for commercial use. However, the environmental issues raised by these techniques have been brought to the world's attention. Nowadays, green synthesis of ZnO nanoparticles is of particular interest in the research field aiming to mitigate environmental problems. In this green approach, natural based materials such as plant extract, microbes, fungus and algae are used as bio-reductants and bio-stabilizers due to their enrichment in bioactive phytochemicals. Numerous studies have proven that the green synthesis is facile and feasible to produce ZnO nanopowder with advanced properties as compared to the chemically synthesized ZnO nanoparticles. In order to make the green synthesized ZnO nanoparticles more applicable in a wide range of uses, surface modification using metal and non-metal ions are applied to alter and improve the properties of ZnO nanoparticles. The findings available currently represent an excellent initial step towards the promising green approach in the synthesis of ZnO nanoparticles and additional work should be undertaken to exploit the application of green synthesis in the commercial platform. Graphical Abstract: ga1 Highlights: Various synthesized pathways of zinc oxide for environmental application are reviewed. Progress on the green synthesized zinc oxide using natural-based materials is summarized. Recent works on various surface modifications and applications of green synthesized zinc oxide are discussed. Mechanism and future prospects of green synthesized zinc oxide are highlighted.